(3GdWH GdQjGVj h cQI GdjOs - (3QjGV GSGeIs ((3GdbGgQIs (3eQcR GdcJGH ddfTQs, 1999)
(3jMJhj Ydi GdeJWdHGJ GdegGQjI GdaSjhdhLjI h cjajI GdEYOGO GdHOfj ddGYH cQI GdjO ,eQcRG Ydi GdfXGe GdZPGFj GdSdje GdPj jLH EJHGYg ,hGdUMI GdYGeI ddGYH h CgejI Gdfhe h GdQGMI ,ceG JMOK Yf hGLHGJ CNUGFj GdWH GdQjGVj , eJWQbG dCfhGY EUGHGJ GdedGYH(B.s
Keywords: (3cQI GdjOs